ANALISIS PEMAHAMAN MAHASISWA PPS UNM BERPANDU TEORI PIRIE-KIEREN DALAM MENYELESAIKAN MASALAH PEMBUKTIAN PADA TEORI GRUP DITINJAU DARI GAYA KOGNITIF DAN ADVERSITY QUOTIENT - Fauziah Hakim (PEDAMATH: Journal on Pedagogical Mathematics, 2019)
The research aims to describe PPs UNM (Postgraduate Program of State University of Makassar) students’ understanding guided by Pirie-Kieren theory in solving proving problem in group theory based on cognitive style (field independent and field dependent) and adversity quotient (climber, camper, and quitter). The conclusion based on the test and interview results are: (1) the levels of understanding achieved by FI-Climber subject are the primitive knowing, image having, property noticing, formalising, and organising; (2) the levels of understanding achieved by FI-Camper subject are the primitive knowing, image having, property noticing, formalising, and organising; (3) it is not discovered the subjects who have field independent cognitive style and low AQ (quitter); (4) the levels of understanding achieved by FD-Climber subject are primitive knowing, image having, formalising, and organising; (5) the levels of understanding achieved by FD-Camper are primitive knowing, image having, and formalising; (6) it is not discovered the subjects who have field dependent cognitive style and low AQ (quitter).